Optimization of hot foam applications for thermal weed control in perennial crops and open-field vegetables - Antonopoulos Nikolaos; Kousta Angeliki; Gazoulis Ioannis; Kontogeorgou Vasiliki; Danaskos Marios; Kanatas Panagiotis; Petraki Dimitra; Travlos Ilias (Open Agriculture)
Thermal weed control can contribute to the development of sustainable integrated weed management systems. This study aimed to optimize hot foam use for thermal weed control in vineyards (Vitis vinifera L.), spinach (Spinacia oleracea L.), and onions (Allium cepa L.). In the vineyard, a randomized complete block design (RCBD) was established with four treatments repeated three times. The treatment list included three different hot foam application rates (13.33, 26.67, and 39.99 L m−2) and a control. The results showed that at the application rate of 39.99 L m–2, the total weed density and biomass were reduced by 91 and 98%, respectively, compared to the control. This treatment was very effective on Conyza canadensis (L.) Cronquist. For both vegetables, four treatments were replicated three times (RCBD): untreated control (SSB-0) and stale seedbed with hot foam for thermal weed control before sowing but after 1 (SSB-1), 2 (SSB-2) and 3 weeks (SSB-3) of seedbed preparation. Compared to the control, SSB-3 reduced the biomass of Sinapis arvensis L., Papaver rhoeas L., and Lolium rigidum Gaud. in spinach by 85, 83, and 91%, respectively, and that of Amaranthus retroflexus L. in onions by 90%. In perennial crops, weed infestation appeared to decrease as the application rate of hot foam was increased. For open-field vegetables, the longer the period between seedbed preparation and pre-sowing thermal weed control, the greater the efficacy of hot foam in a stale seedbed. Further research is required to optimize hot foam as a thermal weed control tool in more cropping systems and environments.